2011
DOI: 10.1371/journal.pone.0020009
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PCR Improves Helicobacter pylori Detection in Patients with Peptic Ulcer Bleeding

Abstract: Background and AimsHistological and rapid urease tests to detect H. pylori in biopsy specimens obtained during peptic ulcer bleeding episodes (PUB) often produce false-negative results. We aimed to examine whether immunohistochemistry and real-time PCR can improve the sensitivity of these biopsies.Patients and MethodsWe selected 52 histology-negative formalin-fixed paraffin-embedded biopsy specimens obtained during PUB episodes. Additional tests showed 10 were true negatives and 42 were false negatives. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 44 publications
2
40
0
3
Order By: Relevance
“…However, to date, very few studies have addressed the usefulness of these techniques, especially very sensitive and specific techniques, such as real-time PCR with an internal control, in bleeding patients (7,19,20,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to date, very few studies have addressed the usefulness of these techniques, especially very sensitive and specific techniques, such as real-time PCR with an internal control, in bleeding patients (7,19,20,24).…”
Section: Discussionmentioning
confidence: 99%
“…However, various studies have shown that in cases of upper gastrointestinal bleeding due to peptic ulcers, PCR techniques for detecting the genome of the microorganism are more reliable than invasive techniques (19,20,24).…”
mentioning
confidence: 99%
“…PCR and real-time PCR are the most frequently used methods. A study from Spain has shown that real-time PCR improves H. pylori detection in patients with peptic ulcer bleeding [40]. They selected 52 histology-negative formalin-fixed paraffin-embedded biopsy specimens obtained during peptic ulcer bleeding episodes and found that among them, 42 were false negatives.…”
Section: Molecular Methodsmentioning
confidence: 99%
“…7 Interestingly, in these situations, a polymerase chain reaction (PCR) was able to detect a low-density infection in a significant number of patients. [8][9][10] The aims of the present study were:…”
Section: Introductionmentioning
confidence: 99%